ANALISIS PENDEKATAN REALISTIC MATHEMATIC EDUCATION TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA : SYSTEMATIC LITERATUR REVIEW - Ayu Lestari, Ryka; Sintiya Safitri, Irma; Efendi Hutagalung, Erwin; Muhammadin Al Fath, Ayatullah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematical problem-solving ability is a core competency that students must master in the 21st century. However, field realities show that this ability remains low due to mathematics instruction that tends to be procedural and lacks contextual relevance. This study aims to analyze in depth the effect of the Realistic Mathematics Education (RME) approach on students’ mathematical problem-solving abilities through a Systematic Literature Review (SLR). The study examined 12 scientific articles published between 2018 and 2026 from various accredited national journals and seminar proceedings. Articles were selected based on strict inclusion and exclusion criteria, then extracted and analyzed using narrative synthesis and thematic analysis. The PRISMA principle was applied to ensure transparency and replicability of the review process. The SLR results indicate that the RME approach consistently exerts a positive influence on improving students’ mathematical problem-solving abilities across elementary, junior high, and senior high school levels. Thirteen out of 14 articles reported significant results with moderate to high improvement. Variations of the intervention, such as RME supported by interactive technology, learning media, and ethnomathematics, further strengthened the effectiveness of the approach. Only one study found no statistically significant difference. This study concludes that RME is an effective and relevant teaching approach that can be widely implemented in Indonesia. The findings are expected to serve as practical recommendations for teachers, curriculum developers, and researchers to enhance the quality of mathematics education in the future.